Diametric Role of the Latency-Associated Protein Acr1 of Mycobacterium tuberculosis in Modulating the Functionality of Pre- and Post-maturational Stages of Dendritic Cells - Amir, Mohammed; Aqdas, Mohammad; Nadeem, Sajid; Siddiqui, Kaneez F.; Khan, Nargis; Sheikh, Javaid A.; Agrewala, Javed N. (Frontiers in Immunology, 2017)
It is instrumental for the Mycobacterium tuberculosis (Mtb) to persist within its host in dormancy. Mtb represses most of its metabolic machinery during latency, but upregulates the expression of latency associated protein alpha-crystallin protein (Acr1). Therefore, it is imperative to understand how throughout dormancy, Mtb employs Acr1 to regulate the host immunity. This study reveals that Acr-1 exhibits divergent effect on the pre and post maturation stages of dendritic cells (DCs). In the current study, we demonstrate that early encounter of bone marrow cells (BMCs) with Acr1 while differentiating into DCs (AcrDCpre), leads to impairment in their maturation. In contrast, when exposed to Acr1 after maturation (AcrDCpost), DCs show augmentation in their activity, secretion of TNF-α, IL-12, IL-6 and activation of T cells. Additionally, AcrDCpost promoted the polarization of naïve CD4 T cells to Th1 cells and Th17 cells and restricted the intracellular growth of Mtb. Furthermore, these DCs upregulated the expression of CCR-7 and exhibited enhanced migratory capabilities. The discrete impact of Acr1 on DCs is mediated through a mechanism involving STAT-1, SOCS-3, ERK, TLR-4 and NF κB signaling pathways. This study reveals the unprecedented role of Acr1 in distinctly modulating the function of DCs at different stages of maturation.